Risk scoring by CHADS2 and CHA2DS2-VASc as predictors for long-term outcomes after surgical ablation for atrial fibrillation. (25th November 2020) - Lauritzen, D; Vodstrup, H.J; Christensen, T.D; Onat, M; Christensen, R; Heiberg, J
Abstract: Background: Following catheter ablation for atrial fibrillation (AF), CHADS2 and CHA2DS2-VASc have utility in predicting long-term outcomes. However, it is currently unknown if the same holds for patients undergoing surgical ablation. Purpose: To determine whether CHADS2 and CHA2DS2-VASc predict long-term outcomes after surgical ablation in concomitance with other cardiac surgery. Methods: In this prospective, follow-up study, we included patients who underwent biatrial ablation - or pulmonary vein isolation procedure concomitantly with other cardiac surgery between 2004 and 2018. CHADS2 and CHA2DS2-VASc scores were assessed prior to surgery and categorized in groups as 0–1, 2–4 or ≥5. Outcomes were death, AF, and AF-related death. Follow-up was ended in April 2019. Results: A total of 587 patients with a mean age of 68.7±0.4 years were included. Both CHADS2 and CHA2DS2-VASc scores were predictors of survival p=0.005 and p<0.001, respectively (Figure). For CHADS2, mean survival times were 5.9±3.7 years for scores 0–1, 5.0±3.0 years for scores 2–4 and 4.3±2.6 years for scores ≥5. For CHA2DS2-VASc mean survival times were 7.3±4.0 years for scores 0–1, 5.6±2.9 years for scores 2–4 and 4.8±2.1 years for scores ≥5. The incidence of death was 20.1% for CHADS2 0–1, 24.8% for CHADS2 2–4, and 35.3% for CHADS2 ≥5, p=0.186. The incidence of AF was 50.2% for CHADS2 0–1, 47.9% for CHADS2 2–4, and 76.5% for CHADS2 ≥5, p=0.073. The incidence of AF related death was 13.0% for CHADS2 0–1, 16.8% for CHADS2 2–4, and 35.3% for CHADS2 ≥5, p=0.031. The incidence of death was 16.8% for CHA2DS2-VASc 0–1, 26.2% for CHA2DS2-VASc 2–4, and 45.0% for CHA2DS2-VASc ≥5, p=0.001. The incidence of AF was 49.6% for CHA2DS2-VASc 0–1, 52.5% for CHA2DS2-VASc 2–4, and 72.5% for CHA2DS2-VASc ≥5, p=0.035. The incidence of AF related death was 12.2% for CHA2DS2-VASc 0–1, 16.0% for CHA2DS2-VASc 2–4, and 42.5% for CHA2DS2-VASc ≥5, p<0.001. Conclusion: Both CHADS2 and CHA2DS2-VASc scores predict long-term outcomes after surgical ablation for AF. However, CHA2DS2-VASc was superior in predicting death, AF, and AF-related death. Funding Acknowledgement: Type of funding source: None